2020
DOI: 10.1002/art.41194
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, Chronic Obstructive Pulmonary Disease, and Subsequent Risk for Incident Rheumatoid Arthritis Among Women: A Prospective Cohort Study

Abstract: Objective. Inflamed airways are hypothesized to contribute to rheumatoid arthritis (RA) pathogenesis due to RA-related autoantibody production, and smoking is the strongest environmental RA risk factor. However, the role of chronic airway diseases in RA development is unclear. We undertook this study to investigate whether asthma and chronic obstructive pulmonary disease (COPD) were each associated with RA.Methods. We performed a prospective cohort study of 205,153 women in the Nurses' Health Study (NHS, 1988… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 58 publications
5
33
1
Order By: Relevance
“…A third finding from this analysis that we initially found surprising was that most types of respiratory diseases were associated with an elevated risk of RA in nonsmokers, but not in smokers, and that there was no positive interaction between the 2 types of exposures. Other studies have found a similar pattern for asthma (15) and air pollution (39), supporting the validity of this result. These are notable findings, as smoking is associated with an increased risk of RA (40), and smoking also confers an increased risk of respiratory diseases as shown in a previous publication (41) and as replicated for individuals without RA in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A third finding from this analysis that we initially found surprising was that most types of respiratory diseases were associated with an elevated risk of RA in nonsmokers, but not in smokers, and that there was no positive interaction between the 2 types of exposures. Other studies have found a similar pattern for asthma (15) and air pollution (39), supporting the validity of this result. These are notable findings, as smoking is associated with an increased risk of RA (40), and smoking also confers an increased risk of respiratory diseases as shown in a previous publication (41) and as replicated for individuals without RA in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…One recent study demonstrated an association between respiratory diseases and ACPA/RF–positive RA (16), though that study did not specifically investigate whether respiratory disease preceded RA or not, and did not take smoking status into account. Another recently published study from the Nurses’ Health Study found an association of asthma and COPD with seronegative RA in women (15), but did not specifically address whether smoking and respiratory disease may confer risk for RA through similar or different mechanisms. Minimal data exist for other types of airway diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale, prospective observational cohorts have become essential resources for investigation into the causes of many diseases, especially common multifactorial diseases with multiple environmental and genetic determinants (1)(2)(3)(4). When they are based on samples representative of the general population, prospective cohorts may also be used for descriptive and epidemiological surveillance purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Inserm UMS 011, Population-based Epidemiological Cohorts, Villejuif, France, 2 Université Paris-Saclay, UVSQ, Univ. Paris-Sud, Inserm, Équipe d'Épidémiologie respiratoire intégrative, CESP, Villejuif, France,3 ClinSearch, Malakoff, France,4 Luxembourg Institute of Health, Luxembourg, Luxembourg,5 Integrated Biobank of Luxembourg (IBBL), Dudelange, Luxembourg,6 Faculty of Medicine, University of Paris, Paris, France…”
mentioning
confidence: 99%
“…Development of COPD in RA patients 29is consistent with the known pulmonary involvement in RA (25,30). Conversely, a recent study identified COPD as a risk factor for RA with the strongest association between COPD and seropositive RA in older smokers (31). Interestingly, individuals who were ACPA positive before RA diagnosis were at increased risk of developing COPD (32).…”
Section: Cigarette Smokementioning
confidence: 63%